2021
DOI: 10.1177/10870547211027640
|View full text |Cite
|
Sign up to set email alerts
|

Distance Learning in Children with and without ADHD: A Case-control Study during the COVID-19 Pandemic

Abstract: Objective: This research involved the parents of ADHD students to explore how their children coped with online distance learning during COVID-19 pandemic and what implications this schooling method had on their emotional and behavioral well-being. Method: Data were collected during lockdown using an online questionnaire addressed to 100 mothers and were compared with 184 matched controls from a national survey launched in the same period. Results: Attention span, spontaneous commitment, and autonomy in distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 50 publications
2
39
0
13
Order By: Relevance
“…During a later stage of the pandemic (March 2021), we found that children with ADHD experienced more challenges with remote learning than their peers without ADHD. This has been corroborated in other recent studies (Becker et al, 2020; Breaux, Dunn et al, 2021; Tessarollo et al, 2021). Furthermore, children with ADHD experienced stronger emotions due to the fear of family illness as a result of the pandemic as compared to their peers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…During a later stage of the pandemic (March 2021), we found that children with ADHD experienced more challenges with remote learning than their peers without ADHD. This has been corroborated in other recent studies (Becker et al, 2020; Breaux, Dunn et al, 2021; Tessarollo et al, 2021). Furthermore, children with ADHD experienced stronger emotions due to the fear of family illness as a result of the pandemic as compared to their peers.…”
Section: Discussionsupporting
confidence: 91%
“…It is possible that this diminished level of concern could lead youth with ADHD to ignore safety precautions and not take infection risk seriously. Finally, parents of a sample of Italian children with ADHD reported their children to exhibit shorter attention span, lower engagement, and lesser independence in participating in distance learning relative to a matched control group (Tessarollo et al, 2021). Pandemic-related disruptions to in-person schooling also have been associated with lower GPAs in a sample of US adolescents with ADHD (Breaux, Dunn et al, 2021).…”
mentioning
confidence: 99%
“…Moreover, during the lockdown, the lack of social opportunities may have had a negative impact on social skills [56], so some young people may have skipped the invitation to study just based on their reluctance to communicate. These concerns support the limited extrapolation of our study findings; for instance, there is evidence in the literature that children and adolescents with physical or mental disabilities survived the COVID-19 pandemic even harder [26,57]. Finally, the way additional questions were formulated may also have affected some study findings, even though not every interview needed these specific additional questions.…”
Section: Strengths and Limitationsmentioning
confidence: 63%
“…The core symptoms of attention-deficit/hyperactivity disorder (ADHD) including inattention, hyperactivity, and impulsivity increased the difficulties in learning among children with ADHD (CADHD) before the COVID-19 pandemic; CADHD encountered more academic problems such as lower grades, grade repetition, and increased school drop-out compared with those without ADHD [ 14 , 15 , 16 , 17 ]. Research has found that CADHD experienced more difficulties in remote learning compared with those without ADHD during the COVID-19 pandemic [ 18 ]; in particular, CADHD exhibited shorter attention spans, less spontaneous commitment, and less autonomy in remote learning during the COVID-19 pandemic [ 19 ]. Studies have confirmed that not only ADHD symptoms but also emotional dysregulation and oppositional defiant disorder (ODD) have negative influences on CADHD’s learning [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%